Crosslinkable polyethylene Manufacture, Properties, Recycling, and Applications - Thomas, Jince; Thomas, Sabu 1960-; Ahmad, Zakiah 1963- (Springer, 2021)
This volume covers various aspects of cross-linked polyethylene (XLPE). The contents include manufacture, morphology, structure, properties, applications, early stage development, cross-linking techniques, recycling process, physical and chemical properties as well as the scope and future aspects of XLPE. It focuses on the life cycle analysis of XLPE and their industrial applications and commercial importance. This book will be of use to academic and industry researchers, as well as graduate students working in the fields of polymer science and engineering, materials science, and chemical engineering.
Keywords: Polymerchemie; B; Polymer Sciences; Chemistry and Materials Science; Polymers; Characterization and Analytical Technique; Characterization and Evaluation of Materials; Werkstoffprüfung; Materials Engineering; Technische Mechanik | Werkstoffkunde; Organische Chemie; Materials science; EngineeringMaterials; Chemistry; XLPE; characterization techniques; water treeing; cable insulation; Cross linked Polyethylene; crosslinking techniques; aging and degradation studies